Good Governance in Regional Official Vehicle Management: Institutional Adaptability and Ethical Accountability - Ahmad Hidir Amin; Ibnu Elmi A. S. Pelu (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study investigates the application of good governance in the management of regional official vehicles within the framework of Islamic Education Management. A qualitative instrumental case study was conducted in Kotawaringin Timur Regency using interviews, document review, and administrative observation. Findings reveal that while formal compliance is high, 88.8% of active vehicles have valid User Decrees, the remaining 11.2% are administratively outdated due to job rotation and delayed updates. This indicates that governance practices remain largely procedural and lack adaptive responsiveness, resulting in gaps in organizational accountability. The primary constraints lie in fragmented data integration between asset and personnel systems and limited inter-unit coordination. From an Islamic Education Management perspective, these conditions reflect incomplete internalization of stewardship (amanah) and professional integrity (itqan) in daily practice. The study concludes that advancing good governance requires integrated digital systems, strengthened organizational adaptability, and the incorporation of ethical values in administrative processes. Conceptually, the research demonstrates that effective public asset governance depends on aligning legal compliance, institutional capacity, and moral accountability within a cohesive governance framework